Sensory evaluation of kokum drinks by fuzzy logic and a simple method. Issue 11 (2nd November 2017) - Sahu, Chandan Kumar; Kadeppagari, Ravi-Kumar
ABSTRACT: Kokum drink formulations were evaluated for their acceptability by fuzzy logic and a new method based on simple calculations. Both the methods showed that the sample containing sugar, cumin, cardamom, and roasted salt at 2, 0.2, 0.2, and 1 g/100 ml juice, respectively, was more acceptable. Quality attributes in general showed under 'satisfactory' in both the methods. When similarity values for the quality attributes of kokum samples 1 to 4 were calculated, the results from both the methods were in agreement with each other. The new method is advantageous since it is simple and gave results similar to that of fuzzy logic.